Determination of the tin stable isotopic composition in tin-bearing metals and minerals by MC-ICP-MS - Brügmann, Gerhard; Berger, Daniel; Pernicka, Ernst (Geostandards and geoanalytical research, 2017)
This study uses MC-ICP-MS for the precise analysis of the stable tin isotopic composition in ore minerals of tin (cassiterite, stannite), tin metal and tin bronze. The ultimate goal is to determine the provenance of tin in ancient metal objects. We document the isotope compositions of reference materials and compare the precision of different isotope ratios and the accuracy of different procedures of mass fractionation correction. These data represent a base with which isotopic data of future studies can be directly compared. The isotopic composition of cassiterite and stannite can be determined after reduction to tin metal and bronze, respectively. Both metals readily dissolve in HCl, but while the solutions of tin metal can be directly measured, the bronze solutions must be purified with an anion exchanger. The correction of the mass bias is best performed with an internal Sb standard and an empirical regression method. A series of Sn isotope determinations on commercially available mono-element Sn solutions as well as reference bronze materials and tin minerals show fractionations ranging from about −0.09‰ to 0.05‰/amu. The combined analytical uncertainty (2s) was determined by replicate dissolutions of reference materials of bronze (BAM 211, IARM-91D) and averages at about 0.005‰/amu.
Online version of record published before inclusion in an issue
Gesehen am 01.08.2017